Proud to not own stocks: How identity shapes financial decisions - Luca Henkel; Christian Zimpelmann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
This paper introduces a key factor influencing households' decision to invest in the stock market: how people view stockholders. Using survey data from the US and the Netherlands, we first document that the overwhelming majority of respondents view stockholders negatively - they are perceived as greedy, gambler-like, and selfish individuals. We then provide experimental evidence that such perceptions of identity-relevant characteristics causally influence decisionmaking: if people view stockholders more negatively, they are less likely to choose stock-related investments. Furthermore, by linking survey and administrative data, we show that negative perceptions strongly predict households' stock market participation, more so than leading alternative determinants. Beyond investment decisions, perceptions predict individuals' polarizing behavior towards stockholders, support for taxation and regulation of financial markets, and misreporting in surveys. Our findings provide a novel explanation for the puzzlingly low stock market participation rates around the world, new perspectives on the malleability of financial decision-making, and evidence for the importance of identity in economic decision-making.
Keywords: G41; G51; D14; D83; 330; identity; perceptions; stock market participation; financial decision-making